PROJECT ``IVOS - INCREASE QUALITY LEVEL IN EDUCATION WITH INTRODUCE INTERACTIVE TEACHING TO SCHOOLS'' - Milan, KLEMENT; LAVRINCIK, Jan (Trends in education, 2009)
The article present project ``IVOS - increase quality level in education with introduce interactive teaching to schools (CZ.1.07/1.1.04/01.0154) ''. This project is cofinanced by the European social fund EU and the state budget of the Czech Republic.
Keywords: interactive white-board; interactive lesson; modernisation.